Comparative inhibitory effects of 4-allylpyrocatechol isolated from Piper betle on Streptococcus intermedius, Streptococcus mutans, and Candida albicans - Phumat, Pimpak; Khongkhunthian, Sakornrat; Wanachantararak, Phenphichar; Okonogi, Siriporn (Archives of oral biology, 2020)
•4-Allylpyrocatechol from Piper betle (APC) is effective against oral pathogens.•APC expresses mechanism of action as bactericidal and fungicidal effects.•Bactericidal action of APC is cell membrane destruction.•APC can potentially inhibit budding or tubing formation of C. albicans.•APC can be considered as a promising potential natural antimicrobial agent. Streptococcus intermedius, Streptococcus mutans, and Candida albicans are harmful oral pathogens and prone to resist chemical antimicrobial agents. Active ingredients from plants are of increasing interest as an alternative. This study aims to compare antimicrobial effects of 4-allylpyrocatechol (APC) extracted from Piper betle on these oral pathogens. Minimum concentration of APC against the tested pathogens was determined using a broth microdilution assay. Killing kinetic study of APC was carried out within 24 h. Morphology of the pathogenic cells was assessed using scanning electron microscopy (SEM). Anti-biofilm was investigated using crystal violet assay and confocal laser scanning microscopy (CLSM). The results showed that the mechanism of inhibition of APC was bactericidal and fungicidal effects. APC at minimum concentration of 400 μg/mL could completely kill Streptococcus and Candida spp., however, the killing rate on S. intermedius and C. albicans was significantly faster than on S. mutans. APC inhibited biofilm formation of C. albicans more efficiently than that of the bacterial cells. Cell morphology from SEM indicated that APC caused bacterial cell membrane destruction and inhibited fungal budding or tubing formation. CLSM images confirmed the killing potential of APC and suggested that bacterial dead cells could be easier washed out than the fungal dead cells. It is concluded that APC potentially inhibits growth and biofilms of oral Streptococcus and Candida spp. in different mechanism of action and killing rate. APC can be considered as a promising agent for preventing and treating dental disorders caused by S. intermedius, S. mutans, and C. albicans.